Impact of infection prevention and control practices, including personal protective equipment, on the prevalence of hospital-acquired infections in acute care hospitals during COVID-19: a systematic review and meta-analysis - Teus, J.K.; Mithen, L.; Green, H.; Hutton, A.; Fernandez, R. (The Journal of hospital infection, 2024)
The COVID-19 pandemic has posed an unprecedented challenge to healthcare systems globally. Personal protective equipment has played a fundamental role in protecting healthcare workers and patients, but its effectiveness in reducing hospital-acquired infections (HAIs) during the pandemic remains a subject of debate. To conduct a synthesis and meta-analysis of the best available evidence of the prevalence of HAIs using a before/after approach. A three-step search strategy was undertaken to locate published and unpublished studies. A search was performed in MEDLINE, CINAHL, Embase, PsycINFO, and Google Scholar. Screening of studies, data extraction and critical appraisal were performed by four independent reviewers. Meta-analysis was conducted using Review Manager. The review is reported in accordance with PRISMA and JBI guidelines for systematic reviews. Fifteen studies were included in the review. Three studies indicated a statistically significant increase in the number of positive cultures during the COVID-19 period compared to the pre-COVID-19 period. Pooled data showed a non-significant decrease in the number of patients with positive cultures in the COVID-19 period compared to pre-COVID-19. There were no significant differences in various bacterial infections except for a significant decrease in respiratory infections. Pooled data for central line-associated bloodstream infections (CLABSIs) indicated a significant increase during the COVID-19 period, but one study reported an increase in CLABSI incidence. The evidence from this review demonstrates a mixed impact of the COVID-19 pandemic precautions on HAIs.